Examining the Antecedents and Consequences of Customers' Trust Toward Mobile Retail Apps in India. Issue 1 (2nd January 2020) - Kaushik, Arun Kumar; Mohan, Geetha; Kumar, Vikas
Abstract: Mobile applications, commonly called 'apps', have become all-pervading nowadays, reducing considerably manual Labor and the time required to complete a transaction. However, despite this convenience, their acceptance and adoption across the social spectrum is low. The authors proposed and tested a model consisting of various antecedents of trust related to (i) the consumer (his/her previous experience and propensity to adopt); (ii) apps (their perceived usefulness, ease of use, and quality); (iii) finally, the organization itself (its reputation and offline presence). Data from 567 respondents using such apps were gathered and examined through structural equation modeling (SEM) techniques. The results confirmed that all the above antecedents (except the consumers' propensity to adopt) significantly affect their trust toward retail apps. There is also a direct and significant influence of perceived trust and risk predicting the consumer's attitude, and intention toward mobile retail apps. Based on the understanding and insights culled from this study, retail organizations (having their respective apps), their associate service providers, and policy makers at large, would be able to form relevant strategies and policies, which in turn would enhance the adoption of mobile apps in India.